Role of Chanakaya in Vishakhadatta’s Mudrarakshasa: Exploring the Challenges and Benefits of Translating Vishakhadatta's 'Mudrarakshasa' (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The play ‘Mudrarakshasa’ is a Sanskrit play written by Vishakhadatta. It is translated into English by K.H. Dhruva ed. Horace Hayman Wilson. It is a historical play. Chanakaya’s overall strategy is successful because of the signet ring given to him by son of Dhanananda. Translation is a strong medium today to understand the original text. Old texts translated into modern languages are very much helpful to those who are not able to understand the original texts. Due to translation of this play from Sanskrit to English, many readers are benefitted and are capable of learning Hindi history. The translation of plays has many problems as the added elements of actors, speech duration and relationship between the art of drama and acting. The translators have to take care of various aspects like final performance, acting tradition, characters and speaking style. Modern translators tend to simplify the sentence structure of the earlier dramas.